ANALISIS PERILAKU PEMECAHAN MASALAH BERDASARKAN TINGKAT SELF-EFFICACY MATEMATIKA SISWA SMP NEGERI 12 PONTIANAK - Romahlina Marbun, Eka Maria; Mirza, Ade; Bistari, Bistari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this study describes the problem-solving behavior based on students’ level of mathematics self-efficacy in accomplishing problem-solving test equation. This study is using descriptive qualitative. The subject of this study is 28 students of IX G class in SMP Negeri 12 Pontianak who had obtained learning material to build flat side space. The result showed that in problem-solving test questions the behavior of subjects with high self-efficacy has a tendency to read repeatedly, record information, determine the strategy, according to the context of the problem, explain all the steps and give an answer reason. However, subject with low self-efficacy have a tendency to record information, according to the context of the problem, include results without read the questions repeatedly and do not specify strategies causing students difficult in explaining all steps and giving reasons for the answer.Keywords: Problem-Solving, Problem-Solving Behavior, Self-Efficacy